2020
DOI: 10.12982/cmujns.2021.002
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pesticide Residues Found in Vegetables and Fruits from Rural and Urban Markets in Upper Northern Thailand

Abstract: Multiple pesticides are used in vegetable and fruit cultivation worldwide, including in Thailand. A survey series on pesticide residues in vegetable and fruit samples sourced from markets in urban and rural areas of upper northern Thailand during 2007–2013. Sixteen different vegetables (n = 412) and 11 different fruits (n = 301) were analyzed for 43 pesticide residues including 20 organophosphates (OP), 6 synthetic pyrethroids, 12 carbamates, 2 abamectins, imidacloprid, dithiocarbamates, and carbendazim. Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Our findings also showed that harvesting/packing tasks were associated with increasing prevalence of respiratory, eye, and skin symptoms. It has been acknowledged that pesticides residues have been detected in Thailand’s vegetable and fruit crops ( 49 ). It is possible that skin contact and dermal poisoning might occur when farmers have direct contact with agricultural crops that had pesticide residues.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also showed that harvesting/packing tasks were associated with increasing prevalence of respiratory, eye, and skin symptoms. It has been acknowledged that pesticides residues have been detected in Thailand’s vegetable and fruit crops ( 49 ). It is possible that skin contact and dermal poisoning might occur when farmers have direct contact with agricultural crops that had pesticide residues.…”
Section: Discussionmentioning
confidence: 99%